2016
DOI: 10.1002/ange.201511985
|View full text |Cite
|
Sign up to set email alerts
|

Commercial Herbicides Can Trigger the Oxidative Inactivation of Acetohydroxyacid Synthase

Abstract: Acetohydroxyacid synthase (AHAS) inhibitors are highly successful commercial herbicides.N ew kinetic data show that the binding of these compounds leads to reversible accumulative inhibition of AHAS.C rystallographic data (to aresolution of 2.17 ) for an AHAS-herbicide complex shows that closure of the active site occurs when the herbicidal inhibitor binds,t hus preventing exchange with solvent. This feature combined with new kinetic data shows that molecular oxygen promotes an accumulative inhibition leading … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
19
0

Year Published

2017
2017
2019
2019

Publication Types

Select...
6

Relationship

4
2

Authors

Journals

citations
Cited by 7 publications
(20 citation statements)
references
References 16 publications
(11 reference statements)
1
19
0
Order By: Relevance
“…In the first phase, the reduction is rapid and involves around 25-30% of the total FAD. This phase could be attributed to the pre-existence of an enzyme-hydroxyethylThDP complex allowing rapid reduction of FAD ox through a long-range electron transfer (7). In the second phase, the FAD reduction rate is lower and follows an exponential decay.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…In the first phase, the reduction is rapid and involves around 25-30% of the total FAD. This phase could be attributed to the pre-existence of an enzyme-hydroxyethylThDP complex allowing rapid reduction of FAD ox through a long-range electron transfer (7). In the second phase, the FAD reduction rate is lower and follows an exponential decay.…”
Section: Resultsmentioning
confidence: 99%
“…Indeed, the quinone reduction activity would allow AHAS to quickly re-establish normal redox conditions in the cell, restoring normal AHAS activity. Besides these differences, there is a commonality between quinones and the commercial herbicides in that their mode of inhibition is time-dependent and linked to oxidation of the FAD red (7). However, the mechanisms leading to this common phenomenon are unrelated.…”
Section: Resultsmentioning
confidence: 99%
“…Previously, we have shown that partial O 2 depletion decreases the amount of accumulative inhibition (9), and that condition was used here for measurement of K i values. For illustration, the inhibition of AtAHAS by PB under partial anaerobic conditions (Fig.…”
Section: Inhibition Of Ahas By the Different Chemical Classes Of Herbmentioning
confidence: 99%
“…Based on these data, several general conclusions could be made: (i) the k iapp and k 3 rates are variable and there is no obvious correlation between k iapp and k 3 values, in agreement with these two rates representing independent events. k iapp represents the apparent rate of inactivation in presence of the inhibitor, whereas k 3 represents the enzyme recovery rate that occurs in absence of inhibitor (9). (ii) The k 3 value of IQ is so small that it is effectively zero.…”
Section: Inhibition Of Ahas By the Different Chemical Classes Of Herbmentioning
confidence: 99%
See 1 more Smart Citation